Խորխե Իկասայի «Փողոցներում» վեպը - Քրիստինա Ղազարյան (ՀՀ ԳԱԱ հրատ.)
В романе “На улицах” Хорхе Икасы отображена тяжелая социально-политическая ситуация, царящая во многих странах Латинской Америки, а также эксплуатация индейца и метиса, бесправие народа. In the novel "In the streets" Icaza describes the social-political unendurable situation of the 20th century in many Latin-American countries, the wild exploitation of the Indians and Metiss and the conditions of these peoples deprived of all rights.
Keywords: Language and Literature